Changes in Northern Elephant Seal Skeletal Muscle Following Thirty Days of Fasting and Reduced Activity - Wright, Traver J.; Davis, Randall W.; Holser, Rachel R.; Hückstädt, Luis A.; Danesi, Christopher P.; Porter, Craig; Widen, Steven G.; Williams, Terrie M.; Costa, Daniel P.; Sheffield-Moore, Melinda (Frontiers in Physiology, 2020)
Northern elephant seals (NES, Mirounga angustirostris) undergo an annual molt during which they spend ~40 days fasting on land with reduced activity and lose approximately one-quarter of their body mass. Reduced activity and muscle load in stereotypic terrestrial mammalian models results in decreased muscle mass and capacity for force production and aerobic metabolism. However, the majority of lost mass in fasting female NES is from fat while muscle mass is largely preserved. Although muscle mass is preserved, potential changes to the metabolic and contractile capacity are unknown. To assess potential changes in NES skeletal muscle during molt, we collected muscle biopsies from 6 adult female NES before the molt and after ~30 days at the end of the molt. Skeletal muscle was assessed for respiratory capacity using high resolution respirometry, and RNA was extracted to assess changes in gene expression. Despite a month of reduced activity, fasting, and weight loss, skeletal muscle respiratory capacity was preserved with no change in OXPHOS respiratory capacity. Molt was associated with 162 upregulated genes including those favoring lipid metabolism. We identified 172 downregulated genes including those coding for ribosomal proteins and genes associated with skeletal muscle force transduction and glucose metabolism. Following ~30 days of molt, NES skeletal muscle metabolic capacity is preserved although mechanotransduction may be compromised. In the absence of exercise stimulus, fasting-induced shifts in muscle metabolism may stimulate pathways associated with preserving the mass and metabolic capacity of slow oxidative muscle.